SISTEM INFORMASI PERSEDIAAN BARANG PADA CV. SRI JATI SUBAH BERBASIS WEB (Information Technology and Telematics, 2013)
- Inventory information system based web technologies to help the processing of data items. Inventory system is currently running in the CV. Sri Jati is the  Subah  still  use manual.To  get problem solving  it created Inventory Information Systems at CV. Sri Jati Subah Based Web.   The purpose of research  is to make inventory information system based web to help solve problems in the inventory system. Systems development method using the system development life cycle phases - phase include: planning,  analysis,  design,  implementation.  To  design such a system is needed as the PHP programming language source code and My SQL as database addressable.   The benefits of this system design is to help provide inventory information quickly, accurately and improve services.   Keywords: Information Systems, Inventory, Items, Web